2000
DOI: 10.1016/s0378-1097(00)00475-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of taxonomic and epidemiological relationships among Campylobacter species by numerical analysis of AFLP profiles

Abstract: Amplified fragment length polymorphism (AFLP)-based profiling was performed on 138 strains representing all named Campylobacter species and subspecies. Profiles of 15/16 species comprised 6 to greater than 100 fragments and were subjected to numerical analysis. The mean similarity of 48 duplicate, outbreak and/or`identical' strain profiles exceeded 94%. Species were clearly distinguished at the 17.90% similarity (S-) level in the dendrogram. Subspecies of Campylobacter jejuni and Campylobacter hyointestinalis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
70
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(89 citation statements)
references
References 14 publications
19
70
0
Order By: Relevance
“…In a recent study by Duim et al (2004), several groups were discerned within this species. A previous study based on numerical analysis of AFLP profiles demonstrated that classical urease-negative and ureasepositive strains form closely related, but distinct, clusters (On & Harrington, 2000). Our results confirm that C. lari is a heterogeneous group as demonstrated in both the rpoB and 16S rRNA gene-derived trees.…”
supporting
confidence: 87%
“…In a recent study by Duim et al (2004), several groups were discerned within this species. A previous study based on numerical analysis of AFLP profiles demonstrated that classical urease-negative and ureasepositive strains form closely related, but distinct, clusters (On & Harrington, 2000). Our results confirm that C. lari is a heterogeneous group as demonstrated in both the rpoB and 16S rRNA gene-derived trees.…”
supporting
confidence: 87%
“…Recently, this method has been adapted for epidemiological typing of C. jejuni and C. coli. These studies demonstrated the subtyping of individual strains, and have already differentiated between two species (Duim et al, , 2000Kokotovic & On, 1999 ;On & Harrington, 2000). In this study, the value of AFLP analysis was determined for the identification and differentiation, at strain level, of nine Campylobacter species and three subspecies belonging to well-defined taxa and representing Campylobacter species that are very important in a veterinary context.…”
Section: Introductionmentioning
confidence: 93%
“…When On and Harrington studied the taxonomic and epidemiological relationship among Campylobacter species by numerical analysis of amplified fragment length polymorphism (AFLP), a high level of genetic diversity in C. lari, particularly amongst UPTC isolates, was identified [117]. Multilocus enzyme electrophoresis analysis, which were shown to be the most successful at discriminating UPTC organisms at the subspecies level, whereas serotyping, phage-typing, antibiogram typing and flagellin typing were unsuccessful [101], also demonstrated that the UPTC isolates (n = 31) isolated from several countries and sources examined are genetically hypervariable and form a cluster separate from the C. lari (n = 3) cluster [94].…”
Section: Atypical Campylobactersmentioning
confidence: 99%